Response of wheat (Triticum eastivum L.), canola (Brassica napus) and medic (Medicago) to a once-off mouldboard and deep tine tillage in the Swartland sub-region of the Western Cape - Van Zyl, Johannes Geldenhuys (Stellenbosch : Stelllenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.